1999
DOI: 10.1037/0012-1649.35.4.904
|View full text |Cite
|
Sign up to set email alerts
|

The development of reasoning with causal conditionals.

Abstract: A total of 512 children in Grades 1 through 6 received a conditional inference task using causal conditionals (If cause P, then effect Q) and a generation of alternatives task. The inference task used premises for which there were few or many possible alternative causes. Results show a steady age-related increase in uncertainty responses to the two uncertain logical forms, affirmation of consequent (AC) and denial of antecedent (DA), and an increase in production of disabling conditions for modus ponens. More … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
92
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 97 publications
(105 citation statements)
references
References 23 publications
11
92
1
Order By: Relevance
“…Both Klaczynski's and Verschueren's dual-process theories agree that producing indeterminate inferences on the AC and DA forms rely on analytic processes. Actually, there is abundant evidence that the production of these indeterminate inferences increases with age from childhood to adulthood, strongly suggesting that, more often than children, adults rely on analytic processes when reasoning from conditional statements (Barrouillet et al, 2000;Barrouillet et al, 2001;De Neys & Everaerts, 2008;Ennis, 1976;Jenveau-Brennan & Markovits, 1999;Markovits, Fleury, Quinn, & Venet, 1998;O'Brien & Overton, 1982).…”
Section: Relationships With Other Dual-process Theoriesmentioning
confidence: 99%
“…Both Klaczynski's and Verschueren's dual-process theories agree that producing indeterminate inferences on the AC and DA forms rely on analytic processes. Actually, there is abundant evidence that the production of these indeterminate inferences increases with age from childhood to adulthood, strongly suggesting that, more often than children, adults rely on analytic processes when reasoning from conditional statements (Barrouillet et al, 2000;Barrouillet et al, 2001;De Neys & Everaerts, 2008;Ennis, 1976;Jenveau-Brennan & Markovits, 1999;Markovits, Fleury, Quinn, & Venet, 1998;O'Brien & Overton, 1982).…”
Section: Relationships With Other Dual-process Theoriesmentioning
confidence: 99%
“…A great deal of research has examined the kinds of inferences that are made under standard deductive instructions, which require a dichotomous evaluation of the certainty of a putative conclusion. Studies in which both children and adults have been looked at (e.g., Cummins, 1995;Janveau-Brennan & Markovits, 1999;Thompson, 1994Thompson, , 2000 have consistently shown a great deal of variation, due to both content and context, in this kind of reasoning. At least two kinds of processes have been posited to exp plain the observed variation.…”
mentioning
confidence: 99%
“…Several studies have shown that the relative number of alternative antecedents that can be readily accessed for any given if-f f then premise with familiar content will affect the kinds of inferences that are made to the AC (and DA) forms (Bucci, 1978;Cummins, 1995;Cummins, Lubart, Alksnis, & Rist, 1991;Janveau-Brennan & Markovits, 1999;Markovits & Vachon, 1990;Thompson, 1994Thompson, , 2000. For example, take the following AC inference: If a brick is thrown at a window, then the window will break.…”
mentioning
confidence: 99%
See 2 more Smart Citations